Prophylactic anticoagulation in sinus rhythm for stroke prevention in cardiovascular disease: contemporary meta-analysis of large randomized trials. (5th July 2021) - Lander, Krystle; Thakeria, Priyanka; Nayyar, Sachin
Abstract: Aims: Anticoagulation with non-vitamin K oral anticoagulants (NOACs) to prevent stroke is a mainstay of atrial fibrillation (AF) management. However, multiple cardiovascular diseases (CVDs) are associated with elevated ischaemic stroke risk even in sinus rhythm. In this meta-analysis, we assess efficacy and safety of prophylactic NOAC agents for stroke prevention in patients without AF. Methods and results: A search was conducted for randomized controlled trials (RCTs) that evaluated an NOAC and control drug (placebo or antiplatelet) in non-AF patients with mixed CVD. The primary efficacy and safety outcomes were ischaemic stroke and major bleeding, respectively. Results were stratified based on primary- and mini-NOAC doses. Thirteen RCTs were identified with a total of 89 383 patients with CVD in sinus rhythm (53 778 on NOAC, 35 605 on control drug; mean age 65.5 ± 2.7 years). Over a mean follow-up of 18.3 months, 1429 (1.6%) ischaemic strokes occurred. Use of NOAC was associated with 26% reduction in stroke [odds ratio (OR) 0.74, 95% confidence interval (CI) 0.62–0.87; 1.1 vs. 1.8 events per 100 person-years], with numbers needed to treat of 153 patients to prevent one stroke. Major bleeding was increased with NOAC (OR 1.74, 95% CI 1.44–2.09; 2.1 vs. 1.0 events per 100 person-years). The weighted net clinical benefit (wNCB, composite of ischaemic stroke and bleeding) did not suggest a favourable effect with any NOAC dose (wNCB for primary-dose: −0.35; mini-dose: −0.06). Conclusion: Current evidence does not support use of NOACs for stroke prevention in non-AF CVD population as risk of major bleeding still exceeds ischaemic stroke benefit. Graphical abstract: